National Differentiation Experience and Citizen Support for Differentiated Integration - Thomas Winzen; Frank Schimmelfennig (JCMS: Journal of Common Market Studies, 2023)
This article examines the determinants of public opinion on differentiated integration (DI) in the European Union (EU). Specifically, it tests whether citizen attitudes are informed by the national experience of opt-outs and exclusions from full participation in EU policies. The study generally finds that support for DI strongly depends on the mode of DI. Even though `multi-speed DI' is only temporary, it is evaluated more critically than durable treaty opt-outs establishing `multi-tier DI'. We suggest that citizens from opt-out countries oppose multi-speed DI out of concern that it would render their exemptions temporary, whereas citizens from new member states tend to be critical towards the often involuntary and discriminatory transitional arrangements that were imposed by the old member states.
Keywords: 330; differentiated European integration; multi-speed integration; multi-tier integration; public opinion